The power of pleasure reading: A narrative inquiry of proficient non-English Learners - Ovilia, Ririn; Asfina, Risda (Universitas Muhammadiyah Sidoarjo, 2022)
A considerable number of studies have shed light on the benefits of ER to English language learning in L2 context. However, there has been no study examining the natural process of how pleasure reading naturally builds up language proficiency. Therefore, this study is intended to divulge the obscure process of how ones unconsciously build up English proficiency by doing pleasure reading. The participants in this study are two non-English learners who have done pleasure reading for, at least, 7 years with no purpose of learning English. Nested in a narrative inquiry methodology, this study examined the participants’ personal stories on the problems they tackle in doing pleasure reading, the gradual process they have been through, their motivation which makes them eager to read, and their unintentionally built up English proficiency. The data were collected through in-depth semi-structured interviews, observation and personal communication. The evidence showed that both participants underwent the language acquisition process in which they were not clued up about the subconscious awareness of language system obtained when reading. They got delectation of reading and achieved language proficiency simultaneously. Conclusively, extensive reading works on improving language proficiency of not only language learners who intentionally read for learning but also those who read only for pleasure. HIGHLIGHTS: The participants underwent the language acquisition process in which they were notclued up about the subconscious awareness of language system obtained when reading. The participants got delectation of reading and simultaneously achieved proficiency invocabulary, reading and listening skills, and grammar. Pleasure reading worked on improving language proficiency of the participants who read for pleasure.